Global Invasion of Thrips parvispinus (Karny) (Thysanoptera: Thripidae) Across Three Continents Associated With Its One Haplotype - Ahmed, Muhammad Z.; Roberts, John W.; Soto‐Adames, Felipe N.; McKenzie, Cindy L.; Osborne, Lance S. (Journal of applied entomology (1986), 2025)
ABSTRACT Thrips parvispinus (Karny) is an exotic pest that has invaded many regions around the world in the last three decades. It was first detected in Florida in 2020 on ornamental plants (Hoya and Anthurium) in greenhouses and subsequently on ornamental plants in residential landscapes (Gardenia) in 2021. However, its first report on open vegetable field crops (Capsicum) in Florida was in 2022. We conducted field surveys and genetic analysis to answer three questions: (1) Is the population of T. parvispinus that invaded Florida the same as the one that has spread globally in the last few decades? (2) Is the host expansion to Capsicum in Florida a new population or the extension of the existing population reported on ornamental plants? and (3) What are the native and invaded distribution ranges of T. parvispinus? We analysed the genetic variation in the mitochondrial gene cytochrome oxidase I (COI) to address these questions. The global genetic diversity analysis of T. parvispinus revealed 18 haplotypes (populations) worldwide based on available data, but only one population (Hap1) invaded three continents: Africa, Europe, and North America. Based on available data, the highest haplotype diversity was observed in India, suggesting India may be part of the presumed native range (South and Southeast Asian countries) of T. parvispinus. Our survey of retail plant stores across 10 Florida counties indicated that plant trade is the source of T. parvispinus in open vegetable field crops and ornamental landscape plants. The outcome of this study will assist with regulatory and management decisions of T. parvispinus in Florida and elsewhere.